Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Mengkonsumsi Rokok Obat Sehat Tentrem Di Kabupaten Ponorogo - Langgeng Satriya Aji Wicaksono; Iza Hanifuddin (Journal of Economics, Law, and Humanities, 2023)
I In Indonesia, there are many cigarette consumers, and entrepreneurs, especially those engaged in cigarette products. The large number of cigarette consumers is a business opportunity that has the potential to continue to grow. This can be seen from the increasing number of new cigarette brands launched in the market and supported by many people who smoke. The desire to consume Cigarettes, Healthy Medicine, and be Peaceful, can be influenced by various factors, such as culture. In this case, it is more cultural; social factors it is more to the group. The personal aspect is more to the lifestyle; psychological factors tend to motivation and belief. This study aims to analyze some of these factors on consumer behavior, which in this case is the consumer of Healthy Medicine Cigarettes Tentrem. This research was conducted in Ponorogo Regency. The research subjects are consumers of Healthy Medicine Cigarettes Tentrem. This study uses several consumer respondents of Healthy Medicine Cigarettes Tentrem as samples. The study used data obtained from interviews. The data obtained will then be analyzed between theory and data in the field. The study results show that these factors influence consumer consumption of Tentrem Healthy Medicine Cigarettes.